2022
DOI: 10.3390/fermentation8010028
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Digestion, Codigestion of Food Waste, and Chicken Dung: Correlation of Kinetic Parameters with Digester Performance and On-Farm Electrical Energy Generation Potential

Abstract: Valorization of agro-food waste through anaerobic digestion (AD) is gaining prominence as alternative method of waste minimization and renewable energy production. The aim of this study was to identify the key parameters for digester performance subjected to kinetic study and semicontinuous operation. Biochemical methane potential (BMP) tests were conducted in two different operating conditions: without mixing (WM) and continuous mixing (CM). Three different substrates, including food waste (FW), chicken dung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Hence, using the same ratio of substrate to working volume, the volume of the substrate used in the OFS was computed, and the electrical energy generation was calculated as shown in Table 10 . In comparison with a previous study on the co-digestion of chicken dung and food waste [ 39 ], the optimum OLRs for both the CSTR (OLR 5) and the AF (OLR 4) produced higher electrical energy generation, whereas the previous study achieved 0.002 kWh [ 39 ].…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…Hence, using the same ratio of substrate to working volume, the volume of the substrate used in the OFS was computed, and the electrical energy generation was calculated as shown in Table 10 . In comparison with a previous study on the co-digestion of chicken dung and food waste [ 39 ], the optimum OLRs for both the CSTR (OLR 5) and the AF (OLR 4) produced higher electrical energy generation, whereas the previous study achieved 0.002 kWh [ 39 ].…”
Section: Resultsmentioning
confidence: 78%
“…The kinetic study was analyzed using Microsoft Office 2021 Excel Solver, where all the kinetic parameters can be predicted for all the models (modified Gompertz model (MG), logistic model (LG), and first order model (FO)). The peak SMP rate and the lag phase can be derived by using the MG and LG; meanwhile, the FO can explain the hydrolysis stage [ 39 ]. In a batch study, the methane generation rate was estimated by the MG model to be proportional to the population growth rate of the methanogens.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the study found that the modified Gompertz model for biogas production was fitted with food waste co-digested with the chicken manure. However, the chicken manure substrate fits well with a logistic model ( Jaman et al, 2022 ).…”
Section: Resultsmentioning
confidence: 95%